Neuroimmune interactions and immunoengineering strategies in peripheral nerve repair. (January 2022) - Wofford, Kathryn L.; Shultz, Robert B.; Burrell, Justin C.; Cullen, D. Kacy
Graphical abstract: Highlights: Immunosuppressive treatments generally reduce nerve regeneration after injury. Macrophages exhibit diverse phenotypes to guide successful nerve regeneration. Immunomodulatory therapies offer promise for treating peripheral nerve injuries. Abstract: Peripheral nerve injuries result in disrupted cellular communication between the central nervous system and somatic distal end targets. The peripheral nervous system is capable of independent and extensive regeneration; however, meaningful target muscle reinnervation and functional recovery remain limited and may result in chronic neuropathic pain and diminished quality of life. Macrophages, the primary innate immune cells of the body, are critical contributors to regeneration of the injured peripheral nervous system. However, in some clinical scenarios, macrophages may fail to provide adequate support with optimal timing, duration, and location. Here, we review the history of immunosuppressive and immunomodulatory strategies to treat nerve injuries. Thereafter, we enumerate the ways in which macrophages contribute to successful nerve regeneration. We argue that implementing macrophage-based immunomodulatory therapies is a promising treatment strategy for nerve injuries across a wide range of clinical presentations.